Effect of the Covid-19 pandemic on the profitability of construction companies: evidence from Bosnia and Herzegovina - Tica, Teodora; Đorđević, Dragana; Saković, Dušan (Anali Ekonomskog fakulteta u Subotici, 2023)
Abstract: This paper aims to demonstrate the theoretical and empirical impact of the Covid-19 virus pandemic on profitability. The analysis was performed on a sample of 131 actively operating companies in Bosnia and Herzegovina between 2014 and 2020. Applying panel regression methodology, an empirical study was conducted. The assessment of fixed-effect model revealed the presence of a negative and statistically significant effect of the coronavirus pandemic on profitability as measured by return on total assets (ROA). The findings validated the curiosity of the construction sector in Bosnia and Herzegovina, suggesting that it is among several sectors with increased demand for its products - residential and non-residential buildings, throughout the pandemic crisis and recession at the beginning of 2020. The results of this study could help construction companies to develop operational performance and risk management in pandemic situations, and the flexibility of their actions in the face of future crises of a similar nature, given that the construction sector has played a crucial role in supplying construction of all types of residential buildings, buildings for industrial production, e.g. factories, workshops, assembly plants, parking garages, warehouses, schools, as well as, hospitals in challenging times and has met the increased demand.